Legal Challenges in Protecting Minority Rights in a Plural Society - Nur Abdurakhman, Raden (Journal of Law and Social Politics, 2025)
Background: Protecting minority rights in plural societies presents complex legal challenges arising from sociopolitical, cultural, and institutional factors. Although international human rights frameworks promote equality and inclusivity, minority groups frequently experience discrimination, marginalization, and limited access to justice due to weak legal implementation and majoritarian dominance Objective: This study aims to analyze the legal obstacles that hinder the effective protection of minority rights in plural societies and to identify legal and institutional mechanisms that can strengthen minority rights within constitutional and human rights frameworks Methods: The study employs a qualitative legal research method using a doctrinal approach. Data are obtained through the analysis of international human rights instruments, national legislation, judicial decisions, and relevant academic literature. A comparative legal analysis is also conducted to examine best practices from different jurisdictions in safeguarding minority rights Results: The findings reveal that the main challenges in protecting minority rights include inconsistencies in national legal frameworks, weak enforcement mechanisms, and the influence of majoritarian politics that often undermine minority protections. In addition, gaps between international human rights standards and their domestic implementation further exacerbate legal vulnerabilities faced by minority groups. Conclusion: The study concludes that effective protection of minority rights requires stronger constitutional safeguards, proactive judicial interpretation, and active engagement of civil society. Legal reforms, institutional capacity-building, and enhanced international cooperation are essential to ensuring non-discriminatory and equitable treatment of minorities in plural societies.